A CO-OPETITION-BASED COLLABORATIVE GOVERNANCE MODEL FOR ENHANCING THE REGIONAL COMPETITIVENESS OF PRIVATE UNIVERSITIES THROUGH HYBRID GOVERNANCE MECHANISMS - Aip Syarifudin; Muhammad Azka Maulana; Sirri Labibah (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2026)
The increasing competition among private higher education institutions (PHEIs) at the regional level often leads to managerial isolation, limiting collective capacity to improve quality and competitiveness. This study aims to develop a co-opetition-based collaborative governance model through hybrid governance mechanisms to enhance the regional competitiveness of private universities. Employing a qualitative multiple-case study design, data were collected from 28 institutional leaders in the Cirebon region through in-depth interviews, institutional document analysis, and reflective field observations. Data were analyzed using an interactive approach involving data condensation, data display, and conclusion drawing. The findings reveal that private universities demonstrate strong readiness to transform competitive relations into a more collaborative and synergistic ecosystem. The study identifies a hybrid governance model integrating formal legal arrangements with informal trust-based relational mechanisms among institutional leaders. A distinctive feature of this model lies in the incorporation of local Islamic values as ethical capital for mitigating inter-institutional conflicts and strengthening collaborative commitment. The findings further indicate that co-opetition practices contribute to resource-sharing efficiency, support accreditation improvement, and strengthen collective bargaining capacity at the regional level. This study contributes to the development of a co-opetition-based governance framework by integrating strategic, relational, ethical, and cultural dimensions into higher education governance practices. Practically, the study highlights the importance of institutionalized inter-university collaboration forums to sustain competitive synergy within emerging regional higher education ecosystems. Keywords: Co-opetition; Collaborative Governance; Hybrid Governance; Islamic Education Management; Regional Competitiveness.   Abstrak Persaingan yang semakin intensif antar Perguruan Tinggi Swasta (PTS) di tingkat regional seringkali mendorong terjadinya isolasi manajerial yang membatasi kapasitas kolektif dalam meningkatkan mutu dan daya saing. Penelitian ini bertujuan mengembangkan model collaborative governance berbasis co-opetition melalui mekanisme hybrid governance untuk meningkatkan daya saing regional perguruan tinggi swasta. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus jamak. Data dikumpulkan dari 28 pimpinan perguruan tinggi di wilayah Cirebon melalui wawancara mendalam, analisis dokumen institusi, dan observasi lapangan reflektif. Analisis data dilakukan secara interaktif melalui proses kondensasi data, penyajian data, dan penarikan simpulan. Hasil penelitian menunjukkan bahwa perguruan tinggi swasta memiliki kesiapan yang kuat untuk mentransformasikan hubungan kompetitif menuju ekosistem yang lebih kolaboratif dan sinergis. Penelitian ini mengidentifikasi model hybrid governance yang mengintegrasikan pengaturan legal-formal dengan mekanisme relasional berbasis kepercayaan antar pimpinan institusi. Keunikan model terletak pada integrasi nilai-nilai Islam lokal sebagai modal etis dalam memitigasi konflik antar institusi dan memperkuat komitmen kolaboratif. Temuan penelitian juga menunjukkan bahwa praktik co-opetition berkontribusi terhadap efisiensi berbagi sumber daya, mendukung peningkatan akreditasi, serta memperkuat daya tawar kolektif di tingkat regional. Penelitian ini berkontribusi pada pengembangan kerangka tata kelola berbasis co-opetition melalui integrasi dimensi strategis, relasional, etis, dan kultural dalam praktik tata kelola pendidikan tinggi. Secara praktis, penelitian ini menegaskan pentingnya institusionalisasi forum kolaborasi antar perguruan tinggi untuk menjaga keberlanjutan sinergi kompetitif dalam ekosistem pendidikan tinggi regional yang berkembang. Kata Kunci: Co-opetition; Collaborative Governance; Hybrid Governance; Manajemen Pendidikan Islam; Daya Saing Regional